The outcome of arthroscopic meniscal repairs: are we doing it right? - Gulamhussein, Mohamed A.; Chaudhry, Samena; Mathur, Keshav (International Journal of Research in Orthopaedics, 2018)
Background: The main aim of our study was to evaluate the outcome of arthroscopic meniscal repairs for all isolated meniscal tears. Methods: A total of 60 patients were included in our retrospective analysis, including all patients with isolated meniscal tears undergoing arthroscopic meniscal repairs from January to December 2015. All those patients who underwent menisectomies were excluded. Outcome measures involved location and type of tear, technique of repair, KOOS scoring system to analyse presence of post-op symptoms as well as the need for repeat surgery. Results: Of the 60 patients, 46 (76.6%) had successful repairs with no post-op repeat symptoms at 6 and 12 months follow up. The remaining 14 patients (23.3%) underwent repeat surgery out of which 5 (35.7%) underwent partial menisectomies, 4 (28.6%) re-repairs, 3 (21.4%) re-repair and partial menisectomy and the remaining 2 patients, MACI procedure. Conclusions: Arthroscopic repair of meniscal tears has shown to be an effective method of treating this surgical entity, meeting success rates comparable to published results. However, the gold standard repair method still needs to be identified.